Bounds on ship deployment in container shipping with time windows. Issue 6 (3rd June 2021) - Ng, ManWo
Abstract: This paper extends and complements the liner shipping literature by examining the ship deployment decision in the presence of time windows at container ports. A set of tight bounds on the number of ships that can be deployed is derived, revealing a number of fundamental insights into the impact of time windows on ship deployment. The bounds in this paper can also enable the extension of single-route shipping models that have appeared in the literature to the system-wide level by taming the increase in computational requirements.